Browsing the Web Using Stacked Three-Dimensional Sunbursts to Visualize Term Co-Occurrences and Multimedia Content - Markus Schedl; Peter Knees; Gerhard Widmer; Klaus Seyerlehner; Tim Pohle (InfoVis'07: Poster Compendium of the IEEE Conference on Information Visualization, 2007)
We present a novel visualization approach that extends the Sunburst technique to the third dimension, which allows for encoding additional data in the height of each arc segment. By stacking a number of such 3D-Sunbursts, we build a user interface for browsing collections of web pages. We apply techniques for web content indexing of multimedia data (text, audio, image, video) and text analysis to create a UI where each layer of the Sunburst stack represents a specific multimedia content type. We call this user interface the Co-Occurrence Browser (COB) and demonstrate its usability on a collection of web pages related to music artists.